Postoperative morbidities with infant cardiac surgery and toddlers' neurodevelopment. Issue 10 (6th July 2022) - Read, Julie; Ridout, Deborah; Johnson, Samantha; Hoskote, Aparna; Sheehan, Karen; Wellman, Paul; Jones, Alison; Wray, Jo; Brown, Katherine
Abstract : Objective: To evaluate the relationship between morbidities after infant cardiac surgery and neurodevelopment and behaviour at age 2–3 years. Design/Setting: A prospective cohort follow-up study, in four paediatric cardiac centres. We excluded children with known syndromes. Home-based neurodevelopmental assessments using the Bayley Scales of Infant and Toddler Development 3rd Edition (Bayley-III) were undertaken in 81 children and secondary outcome measures of development and behaviour were completed by parents. A further 41 families completed the secondary outcome measures remotely. Results: Children were grouped as multiple morbidities/extracorporeal life support (ECLS) (n=19), single morbidities (n=36) and no morbidities (n=59). Group comparisons found that children with multiple morbidities/ECLS, compared with no morbidities, had: (a) lower adjusted mean scores for core Bayley-III composites (none reached the level of statistical significance), with mean differences of cognitive −6.1 (95% CI −12.4 to 0.1) p=0.06, language −9.1 (95% CI −18.6 to 0.3) p=0.06 and motor −4.4 (95% CI −12.0 to 3.1) p=25; (b) greater adjusted odds of at least one low or borderline Bayley-III composite result 4.0 (95% CI 1.0 to 16.0) (p=0.05); (c) greater adjusted risk of an abnormal Ages and Stages Questionnaire (ASQ) result 5.3 (95% CI 1.3 to 21.1) (p=0.03) and a borderline ASQ result 4.9 (95% CI 1.0 to 25.0) (p=0.05); and no difference in the risk of an abnormal Strengths and Difficulties Questionnaire result 1.7 (95% CI 0.3 to 10.4) p=0.58. These outcomes were not statistically different between the single morbidity and no morbidity groups. Conclusions: Children who experience multiple morbidities/ECLS after infant heart surgery are at a greater risk of neurodevelopmental difficulties than their peers who had no complications and should be prioritised for neurodevelopmental follow-up. Abstract : A multi-centre followup study evaluating neurodevelopmental outcomes of children aged 2-3 years who underwent infant cardiac surgery and experienced post-operative morbidities compared to matched controls who did not have complications.